2016
DOI: 10.4103/0972-0707.173197
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of fluoride released and recharged from conventional pit and fissure sealants versus surface prereacted glass ionomer technology

Abstract: Context:The fluoride release of sealants in vitro shows a marked decrease. Giomers are distinguishable from manufactured resin-based sealants and contain prereacted glass-ionomer particles (PRG).Aims:To compare the amounts of fluoride released from the main pit and fissure of a resin-based sealant with that from a Giomer and to assess the abilities of the sealant and the Giomer to recharge when exposed to regular use of fluoride rinse.Materials and Methods:The readings for the fluoride concentration were carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Only one of the new, commercially available, bioactive RBSs (BeautiSealant) was studied in the included in studies [18,20,38,43,49,51]. It was observed that this bioactive RBS released multiple ions, such as Na, Sr, Al, Si and B, which contributed to its strong enamel remineralization effect [49,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one of the new, commercially available, bioactive RBSs (BeautiSealant) was studied in the included in studies [18,20,38,43,49,51]. It was observed that this bioactive RBS released multiple ions, such as Na, Sr, Al, Si and B, which contributed to its strong enamel remineralization effect [49,51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a few studies assessed Sr, sodium (Na), aluminum (Al), silicon (Si) and boron (B) ion release [49,51]. It was noticed that these ions' release was significantly high in the bioactive RBS (BeautiSealant) [20,38,43,49,51]. Nevertheless, one study reported that BeautiSealant released the lowest amount of fluoride [18], and another study stated that there was no significant difference between BeautiSealant and Teethmate F-1 sealants [20].…”
Section: Ions Release Findingsmentioning
confidence: 99%
“…[18,23] These results can be explained by the quick effect of fluoridereleasing ionomeric materials within the first hours, acting initially at the tooth/material interface and remaining constant at lower concentrations. [30] In addition, prevention of demineralization occurred after aging of the material. Aging by thermocycling, as used in this study, might have contributed to lower bacterial adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Alsayed [31] and Salmerón-Valdés [32] conducted in vitro studies to highlight the preventative properties of giomers as coating materials and pit and fissure sealants [31,32].…”
Section: Discussionmentioning
confidence: 99%